2016
DOI: 10.1002/acr.22732
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Interinstitutional Mentoring Program Within Pediatric Rheumatology

Abstract: Objective The small size of many pediatric rheumatology programs translates into limited mentoring options for early career physicians. To address this problem, the American College of Rheumatology (ACR) and the Childhood Arthritis and Rheumatology Research Alliance (CARRA) developed a subspecialty‐wide interinstitutional mentoring program, the ACR/CARRA Mentoring Interest Group (AMIGO). We sought to assess the impact of this program on mentoring within pediatric rheumatology. Methods In a longitudinal 3‐year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…There have been several other successful multiinstitutional mentorship programs piloted in pediatrics, including a successful pilot by the American Society of Pediatric Hematology/Oncology (ASPHO), which provides earlier access to mentorship while still in academic training. Fourteen of the first 16 mentees in the ASPHO program agreed that the program was a rewarding experience .…”
Section: Discussionmentioning
confidence: 99%
“…There have been several other successful multiinstitutional mentorship programs piloted in pediatrics, including a successful pilot by the American Society of Pediatric Hematology/Oncology (ASPHO), which provides earlier access to mentorship while still in academic training. Fourteen of the first 16 mentees in the ASPHO program agreed that the program was a rewarding experience .…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing effective mentorship for ECI may be achieved through a broad-based intervention. For example, the ACR/Childhood Arthritis and Rheumatology Research Alliance (CARRA) Mentoring Interest Group (AMIGO) program, a national inter-institutional mentoring program for pediatric rheumatologists that was established in 2010, has demonstrated concrete benefits of such an intervention in rheumatology mentorship (4, 5). While other opportunities to optimize mentoring and career development exist for rheumatology trainees (Table 1), an inter-institutional mentoring program similar to AMIGO has not been developed for adult rheumatology trainees in the US.…”
mentioning
confidence: 99%
“…In contrast to other mentoring approaches, entry to this programme was based on a competitive open call. Acknowledging the importance of mentor–mentee matching for a successful mentoring relationship,6 33 the mentees were allowed to select the mentor (from the provided list) that best fitted their expectations. The overall satisfaction with the mentors’ feedback and the mentoring experience confirmed that this approach was satisfactory for both parts, and no mismatches were signalled.…”
Section: Discussionmentioning
confidence: 99%
“…Navigating a remote programme with a flexible structure can be challenging, especially in the absence of previous successful mentoring 26. Introductory forms, templates or dedicated information materials have been advocated to overcome such challenges6 34 although most initiatives do not make use of these documents. In line with this, we developed our own IDP as a systematic document covering the whole mentoring process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation